Comparing the Efficacy of Intralesional Saline Versus 35% Trichloroacetic Acid Peel in the Treatment of Atrophic Acne Scar: Treatment of Atrophic Acne Scar - Usman, Kainat; Shahzad, Muhammad Khurram; Hassan, Tahir; Jamil, Muhammad Irfan; Nadeem, Muhammad (Pakistan Journal of Health Sciences, 2025)
Atrophic acne scars are a common sequela of acne vulgaris impact patients’ quality of life. Despite the availability of several treatment modalities, there is a need for simpler and cost-effective approaches. Objective: To compare the efficacy of intradermal normal saline versus trichloroacetic acid (TCA) in treating atrophic acne scars. A randomized controlled trial conducted at the Dermatology Department, Sheikh Zayed Hospital, Rahim Yar Khan, from 1st April 2023 to 31st October 2023. Methods: 126 patients were enrolled. Scar grading was based on Goodman and Baron's Qualitative Scar Classification. The Patients Observer Scar Assessment Scale (POSAS) was used by dermatologists. Efficacy was defined as ≥50% improvement in the POSAS. Results: Among 126 participants, the NS group showed significantly greater improvement in PSAS and OSAS scores post-treatment. While total POSAS score reduction was higher in the NS group, the difference was not significant. A ≥50% POSAS improvement was more frequent in the NS group (88.9%) than in the TCA group (73.0%; p = 0.023).Conclusion: This study found that intradermal normal saline is more effective and satisfactory than trichloroacetic acid for treating atrophic acne scars, with greater improvements in scar severity and patient satisfaction.